INSIDE CONTINUOUS IMPROVEMENT - A LITERATURE REVIEW - Daniel Indarto Prajogo (Institute of Research and Community Outreach - Petra Christian University, 2000)
This paper discusses the concept of continuous improvement (CI) by looking beyond what traditionally highlighted in literature concerning continuous improvement or Total Quality Management (TQM). The primary argument put forwarded in the discussion is that despite the undeniable positive results from CI practices, the way these activities are implemented, however, will lead to most programs becoming self-limiting. It needs to be asserted here that this paper is not intended to despise CI, rather, its purpose is limited only to provide a balance on the prevailing positive views toward CI.